THE EFFECT OF VIDEO EDUCATION AND ANEMIA SCREENING ON PRECONCEPTIVE TREATMENT ATTITUDE OF ADOLESCENT WOMEN - Maretta, Megayana Yessy; Andhikatias, Yunia Renny; Umarianti, Tresia; Widyastuti, Deny Eka (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Adolescent women and women of childbearing age are prospective mothers who are responsible for the quality of the babies born. In fact, most of them have poor preconception health quality because they are prone to anemia. Anemia screening is an effort to determine the Hb levels of them so that they can make efforts to prevent and treat anemia as early as possible as a form of treatment during the preconception period. Good knowledge will form good attitudes and behavior in individuals regarding the dangers of anemia and the importance of health care during the preconception period. Video is an educational medium that can increase individual knowledge and attitudes. The objective of this study is to determine the effect of video education and anemia screening on preconception care attitudes for adolescent womenMethods: This type of research is a quasi-experimental before and after with control. The study was conducted on female students at SMA 1 Al Islam Surakarta. Data analysis used statistical test dependent T-test, independent T-test, Mc Nemar, and Chi-Square with the help of SPSS.Result: The research results show that there is a significant difference between the two groups after education with a p value = 0.021. Respondents who were given education with video and anemia screening had the opportunity to increase their attitude by 1.4 times.Conclusion: The conclusion of this study is that video education and anemia screening are effective in improving the attitude of preconception care for adolescent women.